PENGUATAN KAPASITAS PROFESIONALISME GURU SEKOLAH MENENGAH KEJURUAN - Siraj; Marwan; Abubakar Dabet; Taufiq; Alchalil; Fajriana; Sayni Nasrah (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
The quality of teachers will be better if the stakeholders are able to prepare competent teachers, so that teachers can make changes and adapt to the progress of science and technology. The problem experienced by partners is that not all teachers are looking to continue to develop themselves; limited trainings related to competency improvement, capacity building training models that can be implemented in schools. This activity aims to provide an increase in the professional capacity of SMK teachers. Partners in this activity are teachers of SMK Negeri 4 Lhokseumawe. As for the method of implementing the activities carried out by workshops and In House Training. The results of the evaluation of community empowerment service activities have been able to make a real contribution in increasing knowledge, understanding, and increasing the professional capacity of teachers through continuous training activities. The implementation of this service activity is able to help partner teachers in their potential to become professional teachers by participating in ongoing training through workshops and jam sessions. The knowledge, understanding, skills and productivity of teachers have increased through increasing the professional capacity of Vocational High School teachers.